DOI: 10.31274/rtd-180813-12101
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agriculture and the perceptions of high school agriculture teachers in the North Central Region of the United States

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Literature has shown this type of research design is justified because the objectives of the study sought to describe teachers' beliefs, perceptions, topics and methods of teaching a subject (Ary, Jacobs, & Razavieh, 2002;Lawver, 2009;Muma, 2006). Questionnaires have been used to gather information from the target population in this descriptive-correlational research (Dillman, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature has shown this type of research design is justified because the objectives of the study sought to describe teachers' beliefs, perceptions, topics and methods of teaching a subject (Ary, Jacobs, & Razavieh, 2002;Lawver, 2009;Muma, 2006). Questionnaires have been used to gather information from the target population in this descriptive-correlational research (Dillman, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Many previous relevant studies were conducted by using the TRA as framework. Muma (2006) found that the choice of teaching methods by agriculture teachers is partly dependent on the extent to which sustainable agriculture is taught. LaVergne, Jones, Larke Jr and Elbert (2012) revealed that there were statistically significant differences in teachers' perceptions toward the benefits of diversity inclusion.…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
See 1 more Smart Citation